Literary education and digital learning : methods and technologies for humanities studies - Peer, Willie van.; Zyngier, Sonia; Viana, Vander (Hershey, PA : Information Science Reference, 2010)
'This book provides insight into the most relevant issues in literary education and digital learning, covering literary aspects both from educational and research perspectives'--Provided by publisher.
Foreword : lost and found in the reading machine / Michael Toolan -- Authorship attribution and the digital humanities curriculum / Patrick Juola -- Multivariate analysis of stance in fiction : a case study / Lisa Lena Opas-H$1-W[(Bninen -- Literary onomastics and language technology / Lars Borin, Dimitrios Kokkinakis -- Collocation as instrumentation for meaning : a scientific fact / Bill Louw -- tEXtMACHINA, or, how to account for the methodological particularities of the humanities in the e-learning field / Stefan Hofer, RenBauer, Imre Hofmann -- Plays well with others : the value of developing multiplayer digital gamespaces for literary education / Jon Saklofske -- Teaching Shakespeare in the elementary school through dramatic activity, play production, and technology : a case study / William L. Heller -- Afterword : reading through the machine / David S. Miall.s
Includes bibliographical references and index.
Keywords: Literature and the Internet; Literature -- Research -- Data processing; Literature -- Study and teaching -- Technological innovations; Literature -- Computer network resources; Web-based instruction